Improvement of Educational Processes in Specialized Subjects Based on Digital Technologies - B.J. Khursanov (European Science Publishing, 2023)
In the article, information technologies and their didactic possibilities and improvement of education and training processes based on digital technologies are shown. The introduction of modern information technologies to educational-educational processes and the presentation of educational information and the didactic possibilities of ICTs are highlighted.
Keywords: information and communication technologies, computer, lecture, practical training, presentation, multimedia tools, internet, information systems, means of data collection, processing and transmission.